Key issues in education and social justice - Smith, Emma (Education studies, key issues., 2012)
"This book focuses on educational experience as a lifelong and society-wide issue. The author draws on research, policy, and contemporary thinking in the field to provide a comprehensive guide to the educational inequalities that may exist and persist throughout an individual's educational course. Providing an international perspective on different ethnic, gender, and social groups, the book covers a broad range of issues, including:theoretical, policy, and research developments; inequalities that may exist during the years of schooling; government policy; and beyond the school classroom."--Publisher's website.